The Arabic Discourse Markers in the Short Story Arnūb wa-al-Kasl by Aḥmad Samīr - Yusuf, Kamal; Sabilah, Diyanah Hanin; Achnafiyah, Chumaidatul (Al-Ma‘rifah, 2022)
Literature is an expression of art through language media. In general, literary works in Arabic are divided into three, namely prose, poetry, and drama. One of the prose literary works is short story. Discourse markers, which can be words or sentences, are important in generating coherent parts of literature discourse. In this study, the researchers will examine the discourse markers in the short story entitled “Arnūb wa-al-Kasl” written by Aḥmad Samīr (2008). The method used in this study is a descriptive qualitative in which the researchers as the main instrument aimed to describe the Arabic discourse markers used in the short story. The results of this study showed that the following are the discourse markers used in the story: wāw (‘aṭaf and isti’nāf), innā wa-akhawātuhā, kamā, fā’ [‘aṭaf] and ba‘da. For the wāw, it was found 8 words, for innā wa-akhawātuhā it was found 5 words, and for ba‘da it was found in 2 words.